Using Administrative Data to Change Perception about Caregiving and Improve the Evidence Base Related to Volunteering - O'Reilly, Dermot; Rosato, Michael (SSISI, 2017)
The aim of this paper is to illustrate the added value achievable using dynamically linked administrative data sources: to do this by examining in detail a series of studies related to the morbidity and mortality outcomes of caregivers and volunteers in the UK; to show how this data allow novel research questions to be asked and approaches to be derived – for example, in relation to rare health outcomes, or in using the extant data structures to utilise the detail of relationships within families; and lastly, to show how these innovations can generate policy-relevant answers based on robust research. Finally, we review the limitations of the current data, and conclude by making suggestions for improvement in future censuses.
read before the Society, 22 May 2017
Keywords: caregiving; volunteering; United Kingdom; 314.15